Hubungan Penggunaan APD Dengan Infeksi Covid-19 Pada Bidan Di Sekertariat IBI Ranting Tigaraksa - Zefiro Letius, Fairuz; Tirtasari, Silviana; Hendrawan, Siufui (Fakultas Ilmu Kesehatan Universitas Gresik, 2022)
Coronavirus Disease (COVID-19) first reported in Wuhan, China On December 31, 2019. In January 2020, World Health Organization (WHO) declared COVID-19 as a global health emergency. Confirmed cases of COVID-19 in Indonesia until September 21, 2021, amounted to 4 million cases, with death rate of 140 thousand people. This study determine the correlation between the use of PPE with COVID-19 infection in midwives. Analytical research with a cross-sectional design. subjects of this study are midwives who actively treated patients and is an active members of Tigaraksa IBI branch who met inclusion and exclusion criteria totaling 153 respondents, data were collected on March 4, 2022. Average age of respondents was 29 years old. 69 respondents (45.1%) have an education level of D3 and 84 respondents (54.9%) have an education level of S1. The average work experience of each respondent is 6 years, the longest work experience is 32 years and the most recent is 1 year. majority of midwives implemented PPE. 129 out of all respondents (84.3%) implemented PPE and only 24 respondents (15.7%) did not. There were 99 respondents (64.7%) infected with COVID-19 and 54 respondents (35.3%) who were not infected. There were 13 respondents (54.2%) who did not use PPE and were not infected with COVID – 19 and 11 respondents (45.8%) who did not use PPE and were infected with COVID-19. 41 respondents (31.8%) use PPE and are not infected with COVID-19, and there were 88 respondents (68.2%) who use PPE and are infected with COVID-19. The relationship between the use of PPE with COVID-19 infection obtained a significant value of 0.061, there no relationship between the implementation of PPE and COVID-19 infection in midwives at the IBI Branch Tigaraksa secretariat